Ibuprofen Emulgels as Promising Topical Drug Delivery System - A Study of Formulation Design and In vitro Evaluation - Sandeep, D. S. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: Ibuprofen is BCS class-II drug with lower solubility and higher permeability. The present work was undertaken to formulate ibuprofen emulgels with a view to enhance the bioavailability and to make a suitable topical drug delivery system. Methods: Xanthan gum was used as gelling agent in different concentrations. Ibuprofen was dissolved in ethanol and propylene glycol. The oily phase was prepared with liquid paraffin. The formulated emulgels were subjected for appearance, pH, spreadability, swelling index, rheological study, drug content, and drug release parameters, and the optimized batch was evaluated for particle size and in vitro skin irritation study by HET- CAM test. Results: The prepared emulgels showed satisfactory results for the evaluation parameters. The emulgel IG-4 emerged as optimized formulation with higher drug release which had good mean particle size and also found to be non-toxic and non-irritant with the obtained results of HET-CAM test. Conclusion: Emulgel can be promising topical drug delivery approach for ibuprofen to enhance the bioavailability with better patient compliance.